2022
DOI: 10.1038/s41598-022-11683-x
|View full text |Cite
|
Sign up to set email alerts
|

No alteration of back muscle oxygenation during isometric exercise in individuals with non-specific low back pain

Abstract: The aim of our study was (I) To compare back muscle oxygenation and perfusion as well as Biering–Sorensen muscle endurance (BSME) test holding times between chronic non-specific low back pain (CNSLBP) patients and asymptomatic controls matched for age, body mass index (BMI), sex and physical activity, and (II) to investigate factors associated with BSME holding times. Muscle perfusion (tHb) and oxygenation (SmO2) were measured by near-infrared spectroscopy (NIRS) based oximetry in three back muscles during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In their review, Steele et al (2014) concluded that patients with (chronic) LBP have decreased lumbar extensor strength and endurance [74]. This has been confirmed by the recent literature [63,[75][76][77][78][79][80][81][82][83][84][85][86][87]. However, this is not supported by all studies and the effect sizes of differences between individuals with and without CLBP are variable [86][87][88].…”
Section: Back Muscle Strength and Endurancementioning
confidence: 99%
“…In their review, Steele et al (2014) concluded that patients with (chronic) LBP have decreased lumbar extensor strength and endurance [74]. This has been confirmed by the recent literature [63,[75][76][77][78][79][80][81][82][83][84][85][86][87]. However, this is not supported by all studies and the effect sizes of differences between individuals with and without CLBP are variable [86][87][88].…”
Section: Back Muscle Strength and Endurancementioning
confidence: 99%
“…Near-infrared spectroscopy (NIRS) is a spectroscopic technology employing near-infrared (NIR) light for physiological monitoring, including oxygenation status [4], [5], heart rate [6], [7], vascular tone [8], [9], pulse wave velocity [10], [11], and blood pressure [12], [13]. Since the development of the first NIRS device in 1977 [14], researchers have been working to utilize various design strategies, structures, and advanced manufacturing processes for the development of soft, miniaturized NIRS devices.…”
Section: Introductionmentioning
confidence: 99%